How Cognitive Avoidance and Perfectionism Predict Anxiety in Therapy-Seeking Adults - Acar, Zeynep; Kaya, Selin (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to investigate how cognitive avoidance and perfectionism predict anxiety levels in therapy-seeking adults. A correlational descriptive design was used to assess the relationships among cognitive avoidance, perfectionism, and anxiety in a clinical sample of 484 therapy-seeking adults from Turkey. The sample size was determined based on the Morgan and Krejcie table. Participants completed three standardized self-report instruments: the Beck Anxiety Inventory (BAI) for anxiety, the Cognitive Avoidance Questionnaire (CAQ) for cognitive avoidance, and the Frost Multidimensional Perfectionism Scale (FMPS) for perfectionism. Data were analyzed using SPSS version 27. Pearson correlation was conducted to examine the bivariate relationships between anxiety and each independent variable, and standard multiple linear regression was employed to assess the predictive value of cognitive avoidance and perfectionism on anxiety. Descriptive statistics indicated moderate levels of anxiety and high levels of both cognitive avoidance and perfectionism among participants. Pearson correlation results showed significant positive relationships between anxiety and cognitive avoidance (r = .49, p < .01), and between anxiety and perfectionism (r = .41, p < .01). Cognitive avoidance and perfectionism were also significantly correlated (r = .36, p < .01). The regression model was significant, F(2, 481) = 99.84, p < .001, explaining 30% of the variance in anxiety (R² = .30). Both cognitive avoidance (β = .41, p < .001) and perfectionism (β = .28, p < .001) were significant independent predictors of anxiety. The findings highlight the critical roles of cognitive avoidance and perfectionism in predicting anxiety among therapy-seeking adults. Interventions that target maladaptive avoidance strategies and rigid perfectionistic beliefs may be effective in reducing anxiety symptoms in clinical settings.